(untitled) (Pragyaratna प्रज्ञारत्न, 2023)
The aim of this study was to identify the causes of difficulties in learning mathematics for students at the primary level. For this purpose, I selected a primary school in Ru Ru 04 of Gulmi District. I selected four students studying in Lamakharka Jhamadi primary school at grade five by applying purposive sampling. I used phenomenology within qualitative research design. I triangulated the collected data from students, teachers, and the parents of respective students. From this study, I found that language differences, parent’s carelessness, low economic status, an unfavorable school environment, and a lack of practice at home are the main causes of learning difficulties for students in mathematics.